Narratives of Resistance and Repair in Consumer Society. Issue 1 (2nd January 2018) - Mitchell, Scott
Abstract: This article explores consumer practices of repair and reuse via a series of stories; the making of an iPod case, the sharing of Apple repair manuals, the development of a GI Joe computer game, the animation of a robotic dog, and the repair of a laptop computer. Together, these stories reveal how the space of consumption is shaped by a complex combination of physical design, software protection measures, restricted technical documentation and intellectual property laws. Within this highly controlled environment consumers are forced to adopt a tactical approach as they take up the products of mass-production and remake them to match their own desires. In forging unauthorised paths through the consumer environment, practices of repair and reuse challenge established notions of 'proper' use and reveal the commercial forces that shape consumption.